Ameliorative effects of Danshensu from the functional food Salvia miltiorrhiza against arsenic trioxide-induced cardiac toxicity in vivo and in vitro: Involvement of inhibiting the AKT/IKK/NF-κB signaling pathway. (December 2022) - Yang, Yakun; Qi, Jiaying; Wang, Hua; Zhao, Yang; Wu, Yongchao; Wu, Zhonglin; Shi, Jing; Qu, Weizhong; Chu, Li
Graphical abstract: Highlights: Cardiotoxicity of arsenic trioxide limits its clinical utility. Danshensu has anti-oxidant, anti-inflammatory, and anti-apoptotic activities. Danshensu shows the protective effects on arsenic trioxide-induced cardiotoxicity. Protective mechanisms are related to the inhibition of AKT/IKK/NF-κB pathway. Abstract: Cardiotoxicity is a serious side effect of arsenic trioxide (ATO) which hinders its clinical use in cancer chemotherapy. Danshensu (DSS) has potential applications in the food and healthcare industry to promote cardiovascular health. The experiment aims to investigate the effects of DSS against ATO-induced cardiotoxicity and its possible mechanism. Our results demonstrated that DSS improved cardiac dysfunction, alleviated histopathological damage, enhanced antioxidant activity, attenuated cardiomyocyte apoptosis and suppressed inflammation. Further studies showed that DSS prevented ATO-caused activation of NF-κB by inhibiting the phosphorylation of AKT and IKK, degradation of IκBα, and nuclear translocation of NF-κB. In H9c2 cardiomyocytes, DSS significantly increased cell survival rate and inhibited ATO-mediated expression of p-AKT, p-IKKα/β, p-IκBα, and NF-κB. Notably, the efficacy of DSS was synergistically increased by AKT inhibitor GSK690693. To sum up, DSS effectively ameliorated ATO-induced cardiac toxicity in vivo and in vitro, which may be achieved through inhibition of the AKT/IKK/NF-κB pathway.